Physicochemical and nutritional characterization of sweet snacks formulated with Prosopis alba flour - Sciammaro, Leonardo Pablo (2018)
Prosopis alba flour (PAF) is an adequate ingredient for preparing gluten-free sweet snacks of high nutritional value. Therefore, the objective of this work was to use this flour, together with sugar and honey, as agglutinant agent in the elaboration and functional characterization of sweet snacks. Snacks were formulated with ancestral American seeds (22% amaranth, 22% quinoa, 7.8% quinoa) and variable amounts of each of the three agglutinants (48.2% total) according to an experimental design for mixtures with the restriction of non using only PAF as agglutinant. Five formulations were obtained and characterized by color, moisture, water activity and texture parameters. Sensorial attributes of the two best snacks selected by a test of preference (A and E), were determined using a 9 points hedonic scale. Snacks with sugar or sugar from PAF presented after heating the major variation of color. Snacks with PAF presented intermediate values of moisture and higher values of consistency, resilience and elasticity. The snack containing equal amounts of each agglutinant (A) presented equivalent sensory attributes as that elaborated only with sugar (E). Concluding, PAF resulted a suitable ingredient along with sugar and honey for sweet snacks destined to celiac people that also resulted well accepted by consumers.